PELATIHAN KOMUNIKASI DIGITAL ETIS BAGI APARAT DESA DI KELURAHAN KORPRI JAYA DALAM PENANGANAN KONFLIK INFORMASI DI RUANG PUBLIK - Lies Kumara Dewi; Poppy Suryanti; Henny Dewi Laras Ati; Neysa Amallia (Fakultas Pertanian, 2025)
The rapid development of information technology has transformed patterns of social communication and governance, including at the village administration level. This shift has created new challenges, such as the spread of unethical information that may trigger social conflict, as well as limited digital communication skills among local government staff. In response to these issues, ethical digital communication training was conducted for the staff of Korpri Jaya Subdistrict, Bandar Lampung City. The training aimed to enhance their competence in managing public communication based on digital ethics and to raise awareness of the importance of using polite, informative, and inclusive language in online spaces. The training applied a participatory approach through outreach activities, interactive discussions, and practical simulations of digital communication. Participants were involved in analyzing real cases related to the spread of sensitive information and were trained to develop strategies for handling conflicts arising from digital issues. As a result, the staff showed significant improvement in their ability to use digital media wisely and responsibly, in accordance with principles of truthfulness, fairness, and proper conduct. Internal coordination within the subdistrict office also improved, particularly in managing official information channels. The social impact included enhanced harmony between staff and the community, along with the growth of a more open, transparent, and inclusive communication culture. The training not only strengthened individual capacities but also helped build public trust in more accountable and transparent local governance. This training model has the potential to be replicated in other regions with adjustments to local contexts as a strategic effort to build ethical, communicative, and adaptive governance in the digital era.